2020
DOI: 10.1177/0003134820943568
|View full text |Cite
|
Sign up to set email alerts
|

Breast Hematoma: An Under-Recognized and Under-Reported Female-Specific Traumatic Injury and Its Clinical Significance

Abstract: Female-specific traumatic injury patterns have not been well researched and are potentially not well documented. Our aim was to examine the prevalence of breast hematomas (BHs) after blunt chest trauma, and to evaluate if there were risk factors associated with BH requiring intervention. A retrospective review from 2013 to 2018 was performed, identifying female patients ≥18 years sustaining blunt chest trauma. BH was defined as the presence of a collection of blood within the breast parenchyma, and clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
2
6
1
Order By: Relevance
“…The majority of prior research is comprised of case reports and/or only evaluates a single mechanism of breast injury. [2][3][4][5][6][7][8] In this study of nearly 900 patients nationwide, we found that patient characteristics, type of surgical intervention, and outcomes varied significantly between blunt trauma, penetrating trauma, and burn patients. For example, mastectomy was the most common surgery after burn injuries, while laceration repair and mastotomy were more common following penetrating or blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of prior research is comprised of case reports and/or only evaluates a single mechanism of breast injury. [2][3][4][5][6][7][8] In this study of nearly 900 patients nationwide, we found that patient characteristics, type of surgical intervention, and outcomes varied significantly between blunt trauma, penetrating trauma, and burn patients. For example, mastectomy was the most common surgery after burn injuries, while laceration repair and mastotomy were more common following penetrating or blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of prior research is comprised of single-institution case studies and investigations of only one mechanism of trauma or injury type. [2][3][4][5][6][7][8] The purpose of this study was to define the incidence, mechanism/burden of injury, interventions, and outcomes after breast injuries requiring surgery on a national level. We hypothesized that patient demographics, surgical procedure incidences, and outcomes would differ significantly based on mechanism of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Breast trauma is an often under-recognized injury, particularly in female polytrauma patients, and can be a clinically relevant source of bleeding leading to significant morbidity such as hemorrhagic shock [ 5 , 6 ]. Reports have shown that 17% of patients with breast hematomas require interventions ranging from multiple blood transfusions, angioembolization, or operative intervention [ 7 , 8 ]. One single-site trauma center study found an association between female blunt breast trauma and elevated injury severity (ISS) scores [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research on traumatic breast injuries is limited due to the failure to document and distinguish between breast trauma and chest trauma. 1 Limitations of this study include the retrospective nature, single center, and small sample size. Future prospective studies are needed to further characterize traumatic breast injuries to develop prevention strategies and appropriate management plans.…”
mentioning
confidence: 95%
“…Clinically significant breast hematomas requiring intervention occur more commonly in blunt force trauma in an older patient population. 1 Surgical interventions are not common but may be associated with severity and mechanism of trauma. Burns were shown to have a higher mortality rate and length of hospital stay compared to blunt or penetrating trauma.…”
mentioning
confidence: 99%